Key Factors in the Application of Sharestart to Enhance the Learning Attitude of Students - Luo, Yu-Zhou; Fang, Zhen; Sun, Long-Jie; Zhu, Jie (Frontiers in Psychology, 2021)
Under the background of globalization and the popularity of distance learning ande-learning channels provided on the Internet, teaching methods that encourage the self-directed learning of students are becoming popular. There is an increasing number of domestic teachers joining in the practice for change. The various teaching methods that make the students acquire critical thinking skills can be summarized as learning by doing, critical thinking learning, multiple assessments, team discussion teaching, and cooperative learning. With the teachers of the universities in Shanghai as the questionnaire analysis objects, a total of 360 copies of questionnaires were distributed, and 256 valid copies were retrieved, with the retrieval rate of 71%. The research results are summarized as follows. (1) The “mental adaptation and engagement of students” is the most emphasized dimension, followed by the “professional development of teachers,” “administration and parent support,” and “material and teaching strategy.” (2) The top five emphasized indicators, among 14, are the ordered cultivation of self-study and thinking habits, the development of the professional community for the collaborative lesson study of teachers, the support and cooperation of the president and the administration, adoption of heterogeneous grouping, and co-learning, discussion and cooperative learning. According to the results, it is expected to propose more definite practice directions for teachers intending to attempt such a teaching method, as well as provide some specific suggestions for the first movers of Sharestart.